Pengembangan E-Media Pembelajaran Interaktif berbasis Problem Solving pada Mata Pelajaran Dasar Listrik dan Elektronika - Dasril Chaniago; Usmeldi Usmeldi (Jurnal Pendidikan Teknik Elektro, 2020)
This research on the development of electronic media or e-media for interactive learning is motivated by the limited number of interactive media used by teachers in the learning process, resulting in low student learning outcomes or not meeting the Minimum Completeness Criteria (KKM) in Basic Electrical and Electronics subjects. The research objective is to produce interactive e-learning media in Basic Electrical and Electronics subjects that are valid and practical to increase the learning interest of students in SMK. This type of research is the development of Research and Development (R&D) with a 4-D model (define, design, develop, and disseminate). The subject of this research is interactive e-media learning using problem-solving in Basic Electrical and Electronics subjects. Respondents for practicality trials in this study were students of class X TITL 1 and teachers of Basic Electrical and Electronics subjects. The validation sheet data collection was given to two Electrical Engineering lecturers and a Basic Electrical and Electronics subject teacher. Practical data collection uses a questionnaire distributed to teachers and students of class X TITL 1 in Basic Electrical and Electronics subjects. Based on the results of the research conducted validation of the validator about e-media interactive learning developed with a valid category. The results of the practicality test of interactive e-learning media from subject teachers and 36 students with very practical categories. Thus this research has produced interactive e-learning media that can be used in Basic Electricity and Electronics subjects at SMK Negeri 5 Padang